Effects of Adaptation of In vitro Rumen Culture to Garlic Oil, Nitrate, and Saponin and Their Combinations on Methanogenesis, Fermentation, and Abundances and Diversity of Microbial Populations - Patra, Amlan K.; Yu, Zhongtang (Frontiers in Microbiology, 2015)
This study investigated the effects of garlic oil (0.25 g/L), nitrate (5 mM) and quillaja saponin (0.6 g/L), alone and in binary or ternary combinations, on methanogenesis, rumen fermentation, and abundances of select microbial populations using in vitro rumen cultures. Potential adaptation to these compounds was also examined by repeated transfers of the cultures on alternate days until day 18. All treatments except saponin alone significantly decreased methanogenesis. Ternary combinations of garlic oil, nitrate, and saponin additively/synergistically suppressed methane production by 65% at day 2 and by 40% at day 18. Feed digestion was not adversely affected by any of the treatments at day 2, but was decreased by the combinations (binary and ternary) of garlic oil with the other inhibitors at days 10 and 18. Saponin, alone or in combinations, and garlic oil alone lowered ammonia concentration at day 2, while nitrate increased ammonia concentration at days 10 and 18. Total volatile fatty acid concentration was decreased by garlic oil alone or garlic oil-saponin combination. Molar proportions of acetate and propionate were affected to different extents by the different treatments. The abundances of methanogens were similar among treatments at day 2; however, garlic oil and its combination with saponin and/or nitrate at day 10 and all treatments except saponin at day 18 significantly decreased the abundances of methanogens. All the inhibitors, either alone or in combinations, did not adversely affect the abundances of total bacteria or Ruminococcus flavefaciens. However, at day 18 the abundances of Fibrobacter succinogenes and Ruminococcus albus were lowered in the presence of garlic oil and saponin, respectively. The results suggest that garlic oil-nitrate-saponin combination (at the doses used in this study) can effectively decreases methanogenesis in the rumen, but its efficacy may decrease while inhibition to feed digestion can increase over time.